Influence Wakif's Understanding and Income of Interest in Waqf in PW. Salimah Riau Province - Haniah Lubis; Nur Hasanah; Madona Khairunisa (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
Waqf potential in Indonesia reaches Rp. 180 trillion per year. A very large number, but this potential has not been able to be optimized properly.Some of the challenges that cause this condition include the not yet optimal regulation of waqf, low literacy of waqf, weak capacitynazir waqf, and the use of technology has not been maximized.The aims of this study were: 1) to determine the partial effect of waqif understanding and income on interest in waqf in PW. Salimah Riau Province, 2) determine the simultaneous effect of understanding and waqf income on interest in waqf in PW. Salimah Riau Province, and 3) determine a strategy to increase waqif funding in PW. Salimah, Riau province. The research method is a quantitative method, with technical analysis of hypothesis testing data using the SPSS 26 application. A sample of 30 people, namely PW daily administrators. Salimah, Riau Province. The results obtained partially can be obtained from the results of the t test. The t value is obtainedcountof 1.642 < from ttable2.052, which means that the understanding variable does not have a significant effect on the interest in waqf variable. Meanwhile, income variable (X2) with t valuecount of 6.275 > ttable 2.052, with a significance value of 0.001 <0.05, which means that the income variable has a significant effect on the interest in waqf variable. Simultaneously or jointly the independent variables affect the dependent variable. It can be seen from the results of the F test. The calculated F value is 37.518 > 3.34 with a significance of 0.001 <0.05. It can be concluded that the understanding variable and the income variable together have a significant effect on the interest in waqf by wakif in PW. Strategy in increasing Waqf Collection in PW. Salimah Riau Province including: a) Waqf socialization to administrators, b) Waqf socialization to the community, c) Compulsory Waqf for Management (GARDU), d) Inviting the Community to donate GARDU waqf, e) Movement of 1,000,000, - one million Waqif, and f) A minimum waqf movement of Rp. 2,000, - with a target of one million waqf is one of the newest and flagship programs issued by LWS in an effort to increase waqf funds in an effort to make it easier for people to make waqf.